1998
DOI: 10.1055/s-2007-979344
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bioavailability of Hyperforin from Hypericum Extracts in Rats and Human Volunteers

Abstract: Validated analytical methods suitable for determining hyperforin in plasma after administration of alcoholic Hypericum perforatum extracts containing hyperforin are described. After oral administration of 300 mg/kg Hypericum extract (WS 5572, containing 5% hyperforin) to rats maximum plasma levels of approximately 370 ng/ml (approx. 690 nM) were reached after 3 h, as quantified by a HPLC and UV detection method. Estimated half-life and clearance values were 6 h and 70 ml/min/kg respectively. Since therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(151 citation statements)
references
References 3 publications
12
133
1
1
Order By: Relevance
“…22). This observation substantiates the clinical relevance of our findings and prompts a study of the cancer epidemiology of patients following this antidepressant treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…22). This observation substantiates the clinical relevance of our findings and prompts a study of the cancer epidemiology of patients following this antidepressant treatment.…”
Section: Discussionsupporting
confidence: 87%
“…20). Although a full assessment of the clinical potential of these compounds is not yet possible and must await clarification of issues like absorption, bioavailability, and metabolic fate (21), the pharmacokinetics of Hyp has been thoroughly investigated, revealing that the compound is available upon oral ingestion, with antidepressive therapeutic doses of St. John's wort leading to serum levels of Hyp reaching 0.45 mol/L (22).…”
Section: Introductionmentioning
confidence: 99%
“…The second scan took place 2-4 hours after the last dose (t max for moclobemide was about 2 h, 26 and t max for compounds of St. John's wort formulation was 2-4 h 27,28 ).…”
Section: Treatment Protocolmentioning
confidence: 99%
“…Pharmacokinetic experiments in humans have shown that after a single therapeutic dose of hypericum extract (300 mg, 5% hyperforin), plasma hyperforin levels reach a peak of about 280 nM, with steady-state plasma levels estimated to be approximately 180 nM after a standard treatment regimen (i.e., 300 mg, t.i.d.) (Biber et al 1998). In rats, peak plasma levels of about 690 nM of hyperforin were found after oral administration of 300 mg/kg of the same hypericum extract (Biber et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…(Biber et al 1998). In rats, peak plasma levels of about 690 nM of hyperforin were found after oral administration of 300 mg/kg of the same hypericum extract (Biber et al 1998). Reported IC 50 values for hyperforin as an inhibitor of synaptosomal uptake of serotonin have ranged from 120 nM to 3,300 nM Gobbi et al 1999;Singer et al 1999;Jensen et al 2001).…”
Section: Discussionmentioning
confidence: 99%